Supply chain management practices for SMEs - Kerekes , Vivien; Felföldi , János (Applied Studies in Agribusiness and Commerce, 2020)
In today’s globalized business environment small and medium sized enterprises (SMEs) face many challenges. In order of their survival SMEs need to produce more, at a lower cost, in less time, and with a few defects. They form the most significant group of manufacturing firms and give supports to large companies in many supply chains. In addition, SMEs contribute greatly to entrepreneurship, gross domestic product (GDP) and employment. Despite the fact that micro, small and medium sized enterprises have very important role in business networks, they still have many problems with using supply chain management (SCM) practices. In this research my purpose was to find the best SCM practices as a strategic method to improve SMEs’ performance. First, I give information in general about SCM and the SMEs, then highlight main characteristics of small firms compared to large ones and the reasons why it is essential and efficient to use SCM practices. The article is based on secondary data, using several analysis, surveys, books, journals and my personal experiences collected in this sector. I conclude the research by summarizing my recommendations in connection with SCM practices, the opportunities and barriers. JEL code: M11